Pendidikan Akhlak dan Spiritual di Era Modern dalam Perspektif Imam Al Ghazali - Syaefudin, Syaefudin (Paedagogie, 2026)
This study aims to explore how al-Ghazali's educational concepts can offer solutions to the current moral and spiritual crises confronting today's generation. This research employs a qualitative approach through a literature review, analyzing al-Ghazali's works along with contemporary literature on Islamic education. The indings indicate that al-Ghazali places morality and spirituality at the core of the educational process. He emphasizes the importance of self-purification and character formation as the foundational elements in educating individuals. This perspective is highly relevant in the face of modern challenges, where technological advancement and the flow of information are often not accompanied by ethical and spiritual values. al-Ghazali's educational philosophy strengthens the integration of scientific knowledge and religious values, equipping learners with noble character and moral clarity to navigate modern life without losing their ethical direction.